Top Democrat sees Beijing distrust delaying Hong Kong universal suffrage (BBC Monitoring Asia Pacific, 2010)
On his last trip to Beijing to report duty as the chief executive, Mr Donald Tsang was reportedly told by Prime Minister Wen Jiabao to tackle the deep-level contradictions in Hong Kong. There have in fact been repeated warnings from Beijing leaders that Hong Kong is being confronted by such contradiction and it is suggested that Mr Donald Tsang, as the top political leader of Hong Kong should have the insight in understanding its nature and formulating the necessary strategy to resolve the problem. Our public records clearly show that during the time of the general election of the Legco in 2000, all the then major political parties including the Liberal Party, the Democratic Party and even the DAB all supported dual universal suffrage being implemented in 2007 and 2008. Unfortunately, the overlapping consensus of the Hong Kong political parties representing the whole spectrum of our community was demolished by the NPCSC [National People's Congress Standing Committee] decision in April 2004. The Liberal Party and DAB then conceded that Hong Kong should have dual universal suffrage in 2012 but again that consensus was shattered by another NPCSC decision in December 2007. We need to be assured that the universal suffrage promised to be put in place in 2017 and 2020 will be genuine universal suffrage. The election of the chief executive by universal suffrage in 2017 should not be subject to any vetting or screening of candidates, such that meaningful competition in the universal suffrage may be eliminated. Further, functional constituencies as a form of special franchise for the privileged classes of Hong Kong citizens should be fully abolished at the latest by 2020.